Pengaruh Current Ratio dan Debt To Equity Ratio Terhadap Return On Asset Pada PT Bumi Citra Permai, Tbk. - Ramli; Afriyani; Andriani Yasin, Nurfatwa; Jumria (LPPM STIE Tri Dharma Nusantara - Makassar, 2025)
The Effect of Current Ratio and Debt to Equity Ratio on Return On Asset PT. Bumi Citra Permai, Tbk. Guided by Nurfatwa Andriani Yasin and Afriyani. The purpose of this study is to determine the effect of current ratio and debt to equity ratio on return on asset in PT. Bumi Citra Permai, Tbk. The types of data used are qualitative and quantitative data. The data source used in this study is secondary data. The analysis methods used in this study are descriptive and statistical analysis (multiple linear regression, determination coefficient, correlation coefficient, f-test, and t-test). The multiple linear regression equation is Y= 44,367 – 0,015X1 – 0,396 X2, the determination coefficient is 90.8%, the correlation coefficient is 0.953. The result of this study are that the current ratio and debt to equity ratio have significant affect on return on asset, the current ratio has a negative and significant effect on return on asset, and the debt to equity ratio has a negative and significant effect on return on asset. Thus, the hypotheses in this study Hipotesis 1,Hipotesis 2, and Hipotesis 3 are accepted.